A prospective longitudinal assessment of MRI signal intensity kinetics of non-target muscles in patients with advanced stage oropharyngeal cancer in relationship to radiotherapy dose and post-treatment radiation-associated dysphagia: Preliminary findings from a randomized trial. (January 2019) - ,; Meheissen, Mohamed A.M.; Mohamed, Abdallah S.R.; Kamal, Mona; Hernandez, Mike; Volpe, Stefania; Elhalawani, Hesham; Barrow, Martha P.; Ding, Yao; Wang, Jihong; Davuluri, Raj; Rostom, Yousri; et al.
Highlights: We identified the MRI kinetics of muscles associated with radiation-induced dysphagia. We compared mid- and post-RT SI relative to baseline based on dysphagia status. Radiation injury can be quantified using serial MRI as early as the midpoint of RT. Middle pharyngeal constrictor had the most significant changes among studied muscles. Abstract: Purpose: To assess quantitative signal intensity (SI) kinetics obtained from serial MRI of swallowing muscles as a potential imaging biomarker of radiation-induced dysphagia in oropharyngeal cancer (OPC) patients receiving radiotherapy (RT). Methods: Patients were enrolled under an IRB approved Phase II/III randomized trial. Patients underwent serial MRIs at pre-, mid-, and post-RT. Normalized T1, T1+ contrast (T1 + C), and T2 SI for swallowing muscle volumes-of-interest (VOIs) were collected and delta SI changes (Δ) were calculated. Mid- and post-RT SI relative to baseline were assessed and correlations between radiation dose and percent change in SI were calculated. Independent samples' t-tests were used to compare the percent change of SI between patients divided into two groups based on dysphagia status post-RT. Results: Forty-six patients with stage III/IV HPV+ OPC were included in this study. Relative to baseline, mean T2 and T1 + C SIs for middle pharyngeal constrictor were both significantly higher at mid- and post-RT ( p < 0.004 for all). Superior pharyngeal constrictor also showed a significant increase in T1 + C SI at mid-RT ( p = 0.0004). Additional muscle VOIs showed significant changes post-RT, but not earlier at mid-RT. Both mid- and post-RT doses were significantly correlated with the percent change of normalized T2 and T1 + C SI for examined muscle VOIs (p < 0.002). Mean percent changes of normalized T2 SI at mid-RT relative to baseline for all muscle VOIs were significantly higher in patients who developed grade ≥2 dysphagia relative to patients with no/mild dysphasia (mean Δ%: 8.2% vs 1.9%; respectively, p = 0.002). However, at post-RT, these changes were only significant in T1 SI (11.2% vs −1.3%; p < 0.0001). Conclusion: Signal intensity kinetics of radiation injury can be broadly correlated with the functional muscular defect. Serial MRI during the course of RT may provide an opportunity to quantitatively track muscular pathology for subclinical detection of patients at high risk to develop dysphagia.